(untitled) (American Journal of Business Management, Economics and Banking, 2025)
In an era of globalization and economic integration, Business English has become a crucial tool for professional success. This article explores the current demand for Business English education in Uzbekistan, focusing on its role in facilitating communication with international partners, navigating business documentation, and enhancing branding strategies. The paper reviews the existing infrastructure, including university programs, language courses, and ongoing projects. Through practical observations and sample data, the study reveals gaps in curriculum design, teacher preparedness, and the need for digital resources. It concludes with strategic recommendations for aligning Business English instruction with real market needs.